PENGEMBANGAN KECERDASAN EMOSIONAL DI SMA PRIMAGANDA BULUREJO DIWEK JOMBANG - solechan zidni (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2019)
This study discusses the student’s emotional Intelligence development at SMA Primaganda Jombang. It is the intelligence to manage emotionally in the form of self-regulation, self-awareness, motivation, empathy and social skills. The results of this study 1. The development of students emotional intelligence in SMA Primaganda Jombang is done through: a) Habit, such as building self- confidence; Wiridan amaliyah of asmaul khusna ; Spiritual approach, b) rewarding students who are excel c) encouragement students tolearn more, d) providing a good example for students e) giving social skills, it is dealing good to others, f) school rules must be obeyed by students. 2. Supporting and inhibiting factors in developing emotional intelligence of participants: a) differences in the types of previous education, b) multilateral (different of background) both in terms of culture and characters among them, c) the students bigotry which is attached to them, and the supporting factors are: a) good relation with formal schools, b) The majority of students are pupils c) good teacher, d) good facilities in supporting the students’ emotional intelligence.